The Patterns of Inheritance in Early-Onset Dementia: Alzheimer's Disease and Frontotemporal Dementia. (May 2015) - Jarmolowicz, Anna I.; Chen, Huei-Yang; Panegyres, Peter K.
Aim: To investigate the patterns of inheritance and gene mutation status in early-onset dementia (EOD). Methods: Data were collected on 202 consecutive patients presenting to an EOD clinic. Early-onset Alzheimer's disease (EOAD, n = 120) and early-onset frontotemporal dementia (EOFTD, n = 82) were studied. Results: The majority of participants, 72.5% with EOAD and 74.4% with EOFTD, did not have a positive family history of dementia. An autosomal dominant pattern of inheritance was observed in 14.2% of patients with EOAD and 13.4% of patients with FTD. Of those with an autosomal dominant pattern of inheritance, 11.8% of EOAD and 45.5% of FTD probands had known pathogenic mutations. Only 1.6% of the total population of EOAD and 7.3% of EOFTD possessed known gene mutations. Conclusion: Early-onset dementia does not appear to be a strongly inherited autosomal dominant condition. The majority of patients were sporadic. Known mutations were uncommon and do not explain the total autosomal dominant burden.